2017
DOI: 10.1016/s0168-8278(17)31971-2
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of serum lipid profile after direct acting antiviral treatment

Abstract: Host lipid metabolism influences viral replication and lifecycle of hepatitis C virus. Our aim was to evaluate changes in glucose and lipid metabolism of patients with chronic hepatitis C after therapy with direct acting antivirals (DAA). Material and Material and Material and Material and Material and methods. methods. methods. methods. methods. We considered patients consecutively treated between January and November 2015 recording clinical data at baseline and week 24 of follow-up. Frozen serum samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
2
7
1
Order By: Relevance
“…In this study, we analyzed the dynamics of circulating lipid profile in patients treated with DAA for CHC. In line with previous reports (10,12,13,31), total and LDL cholesterol levels increased in parallel to HCV RNA clearance. These changes persisted during the subsequent follow-up, indicating that a different, more 'atherogenic' lipid pattern establishes after CHC cure.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this study, we analyzed the dynamics of circulating lipid profile in patients treated with DAA for CHC. In line with previous reports (10,12,13,31), total and LDL cholesterol levels increased in parallel to HCV RNA clearance. These changes persisted during the subsequent follow-up, indicating that a different, more 'atherogenic' lipid pattern establishes after CHC cure.…”
Section: Discussionsupporting
confidence: 92%
“…Also, HCV clearance was shown to be associated with a reduction of atherosclerosis lesions in the short term (38). These data are apparently in contrast with the establishment of a more atherogenic lipid pattern emerging from this and prior studies (10,12,13 risk showed that, at least in the short term, cardiovascular risk after DAA treatment does not change despite of the increase in total and LDL cholesterol levels. Time of observation is probably too short to detect important modifications of these parameters, but it is probable that overweight and particular visceral obesity play a role in the lipid pattern changes during and soon after DAA treatment.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations